Heavy metals in Shrimp pond and Shrimp muscles - Ling, T. Y.; Malini, M.R.; Lee, Nyanti (Proceedings of NREM & ESH 2007, Kuching, 2007)
Sarawak is a key producer of cultured black tiger shrimp (Penaeus monodon) in Malaysia. However, knowledge on the heavy metals is shrimp and culture ponds were lacking in literature. Therefore, in this study, concentrations on selected heavy metals in shrimp pond sludge, pond water, shrimp feed, and shrimp muscles from two farms in different locations were investigated. Results indicated that heavy metals concentrations of sludge nearer to the center of the pond were higher than those at the edge of the pond and Zn and Mn concentrations were higher than Cu and Cd. In pond water, concentrations of heavy metals were less than 0.2 mg/L escept for Mn in Farm 2 which was much higher. For shrimp feed, Zn and Mn concentrations were higher than Cu and Cd. The concentration of Cu in feed was different between the two farms. In the shrimp muscles, Zn concentration was the highest followed by Cu. The concentration of heavy metals such as Zn and Cu in the shrimp muscles was not significantly correlated with that in the feed, sludge or water. The concentrations of Zn, Cu and Cd in the shrimp muscle did not exceed the maximum permissible limits of the Malaysian Food Act.